2019
DOI: 10.1136/jmedgenet-2018-105713
|View full text |Cite
|
Sign up to set email alerts
|

Review of the scientific evolution of gene therapy for the treatment of homozygous familial hypercholesterolaemia: past, present and future perspectives

Abstract: Familial hypercholesterolaemia (FH) is a devastating genetic disease that leads to extremely high cholesterol levels and severe cardiovascular disease, mainly caused by mutations in any of the main genes involved in low-density lipoprotein cholesterol (LDL-C) uptake. Among these genes, mutations in the LDL receptor (LDLR) are responsible for 80%–90% of the FH cases. The severe homozygous variety (HoFH) is not successfully treated with standard cholesterol-lowering therapies, and more aggressive strategies must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Gene therapies for HoFH are under development and may offer new alternatives in the treatment of HoFH [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapies for HoFH are under development and may offer new alternatives in the treatment of HoFH [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial cells (macrophages, pericytes, and smooth muscle cells) take up these particles in an unregulated manner bypassing the specialized LDL receptor [3][4][5]. The mechanism of interaction of native (unmodified) LDL with a specific cell receptor is currently well known [5][6][7][8]. This interaction does not lead to excessive deposition of intracellular lipids since the lipid components of LDL are utilized by cells, and the excess is removed.…”
Section: Introductionmentioning
confidence: 99%
“…Two subtypes of FH are known as homozygous (HoFH) and heterozygous FH (HeFH). Recent data have shown that the incidence of homozygotic FH is 1 in 1,000,000, while HeFH is 2000 times more frequent (1:500) [ 49 ]. LT is considered to be a gold standard treatment, but it is invasive and may cause other complications [ 50 ].…”
Section: Familial Hypercholesterolemiamentioning
confidence: 99%
“…LDL apheresis is another therapeutic option, limited due to high costs and difficulty to apply [ 51 ]. Furthermore, administration of statins, such as atorvastatin, only reduced the plasma LDL-C level by 10 to 25% [ 49 ].…”
Section: Familial Hypercholesterolemiamentioning
confidence: 99%